Testing device and method for blocking rock fractures by soybean urease induced calcium carbonate deposition technology
By designing a test device for blocking rock fractures, combined with soy urease-induced calcium carbonate deposition technology, the problem of insufficient testing of rock fractures in the existing technology is solved, and the effect of blocking and emphysema reduction of rock fractures is achieved. Visualization and simulation.
Patent Information
- Application Number
- CN202411541496.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art has shortcomings in blocking and reducing permeability of rock fractures, especially in the absence of effective testing devices and methods when simulating rock fractures of different types and parameters.
A test device for soy urease-induced calcium carbonate deposition technology for blocking rock cracks was designed, including upper rock test blocks made of transparent materials, fracture simulation components that simulate tension and shear cracks, and slurry sealing components. To achieve visual observation of rock fissures and tests of soy urease-induced calcium carbonate deposition.
This device can intuitively visually observe the sealing and impermeability effect of soy urease-induced calcium carbonate deposition on rock fractures, and can simulate rock fractures of different types and parameters, help analyze the impermeability effect of soy urease-induced calcium carbonate deposition technology under different conditions .
Smart Images

Figure CN119413677A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of underground engineering, and in particular to a testing device and method for using soybean urease-induced calcium carbonate deposition technology to seal rock fissures. Background Art
[0002] There are rock cracks of different types, openings and roughnesses inside the rock mass. The existence of these cracks reduces the strength of the rock mass and increases the permeability of the rock mass, which brings safety hazards to underground rock engineering. Cement slurry is usually used to seal rock cracks in underground rock engineering to reduce the permeability of the cracks and thus enhance the strength of the rock mass. However, cement slurry is an alkaline material, which pollutes the environment greatly. In addition, the viscosity of cement slurry is relatively high and it cannot penetrate into rock cracks with small openings. The anti-seepage effect is greatly affected by the rock crack environment. As a new type of reinforcement and anti-seepage technology, soybean urease-induced calcium carbonate deposition (SICP) technology has great application prospects in sealing rock cracks. By injecting cementing fluid (urea and CaCl2 solution) and urease solution into rock cracks, calcium carbonate crystals will be generated inside the rock cracks, thereby achieving the purpose of strengthening rock cracks and reducing crack permeability. SICP slurry has strong permeability and can be applied to rock cracks of different scales and types, without pollution to the environment.
[0003] In underground rock engineering, rock fissures vary in size, opening and roughness, and the generation mechanisms of rock fissures are also different. They are mainly divided into tension type fissures or shear type fissures. The reinforcement and seepage resistance effect of SICP grouting technology on rock fissures is closely related to the rock fissure parameters (openness, roughness) and fissure types. However, at present, there is a lack of experimental equipment and test methods for SICP grouting for different rock fissure types and fissure parameters. Summary of the invention
[0004] In view of the defects of the above-mentioned prior art, the technical problem to be solved by the present invention is to provide a testing device and method for using soybean urease-induced calcium carbonate deposition technology to seal rock cracks, which can intuitively and visually observe the sealing and permeability reduction effect of soybean urease-induced calcium carbonate deposition on rock cracks, and can simulate the crack opening in both tension-type cracks and shear-type cracks of rock blocks.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: a test device for sealing rock cracks using soybean urease-induced calcium carbonate deposition technology, comprising a sample, a crack simulation component and a slurry sealing component, wherein the sample is composed of an upper rock test block and a lower rock test block that match each other, and the upper rock test block is made of a transparent material;
[0006] The crack simulation component includes an upper shear box, a lower shear box and a base, wherein the upper shear box is used to clamp the upper rock test block, and the lower shear box is used to hold the lower rock test block, and a gap is left between the upper and lower shear boxes when they are respectively installed on the upper and lower parts of the specimen, and a vertical support rod and a horizontal rolling groove are provided on the base, and both the vertical support rod and the horizontal rolling groove are marked with scales; the upper shear box is slidably connected to the vertical support rod to enable the upper rock test block to move up and down relative to the lower rock test block to simulate the tension type crack of the rock block, and the lower shear box can roll on the horizontal rolling groove to enable the lower rock test block to move left and right relative to the upper rock test block to simulate the shear type crack of the rock block;
[0007] The slurry sealing assembly includes an end guide block, an end water sealing pressure plate, an end water sealing rubber pad, a side water sealing rubber pad and a side water sealing pressure plate arranged in pairs; the end guide block is provided with a fluid channel inside and is fixedly installed at the left and right ends of the specimen, the end water sealing rubber pad is arranged between the end guide block and the end water sealing pressure plate, and the end guide block and the end water sealing pressure plate both adopt a split structure corresponding to the upper shear box and the lower shear box, the end water sealing rubber pad adopts an integrated structure and leaves a redundant amount bulging outward at the upper and lower split positions; the side water sealing rubber pad and the side water sealing pressure plate are both arranged on the front and rear sides of the specimen to seal the gap between the upper shear box and the lower shear box; the side water sealing rubber pad and the left and right ends of the side water sealing pressure plate are both provided with extensions to ensure that when the lower shear box moves to the left and right extreme positions relative to the upper shear box, it can still flexibly overlap with the two ends of the end water sealing rubber pad to form a closed storage chamber.
[0008] Preferably, the upper rock test block is cast with a transparent resin material, and the lower rock test block is cast with a real rock material.
[0009] Preferably, the upper shear box is fastened and fixed to the upper rock test block by a tightening bolt a. A rectangular observation port is provided on the top of the upper shear box, which cooperates with the transparent upper rock test block to realize the visual observation of the slurry flow and calcium carbonate deposition inside the fracture surface; the upper shear box is slidably connected to the vertical support rod through a horizontal connecting rod with a sleeve at the end, and is fixed by tightening the tightening bolt b set in the sleeve; four vertical support rods are provided corresponding to the upper shear box, so that the movement of the upper shear box 2 is precise and stable.
[0010] Preferably, a roller is installed in the horizontal rolling groove to realize the horizontal movement of the lower shear box, and the horizontal movement of the lower shear box is realized by a hand-cranked push rod.
[0011] Preferably, the surface of the vertical support rod is marked with scales, and a horizontal scale is provided at the edge of the horizontal rolling groove.
[0012] Preferably, the side water sealing pressure plate is fixed and compressed by an "L"-shaped pressure plate support frame and fastening bolts, and the pressure plate support frame is fixed to the base by fixing bolts.
[0013] Preferably, the end water-sealing rubber pad is made of industrial rubber sheet, and the side water-sealing rubber pad is made of silicone material.
[0014] A test method for plugging rock fissures by using a soybean urease-induced calcium carbonate deposition technology, using a test device for plugging rock fissures by using a soybean urease-induced calcium carbonate deposition technology, comprising the following steps:
[0015] Step 1, simulate the tension type crack opening; install the sample on the crack simulation component, keep the upper rock test block and the lower rock test block in a natural meshing state, regard the crack as being in the initial closed state at this time, and read the scale value h0 of the upper shear box relative to the vertical support rod; keep the lower shear box and the lower rock test block immobile, vertically lift the upper shear box and the upper rock test block, and read the scale value h0′ of the upper shear box relative to the vertical support rod, thereby obtaining a tension type rock crack with a crack opening of Δh=h0′-h0;
[0016] Step 2, simulate the opening of shear type cracks; install the sample on the crack simulation component, keep the upper rock test block and the lower rock test block in a natural meshing state, regard the crack as being in the initial closed state at this time, read the scale value h0 of the upper shear box relative to the vertical support rod, and read the horizontal scale value s0 of the horizontal rolling groove corresponding to the left or right edge of the lower shear box; move the lower shear box and the lower rock block gradually horizontally, read the scale value h0′ of the upper shear box relative to the vertical support rod, and read the horizontal scale value s0′ of the horizontal rolling groove corresponding to the left or right edge of the lower shear box, thus reaching a shear type rock crack with a crack shear displacement of Δs=s0′-s0 and a crack opening of Δh=h0′-h0;
[0017] Step 3: First test the permeability coefficient of rock fractures before grouting reinforcement to form a control group; Figure 4 As shown, a seepage test system is used to adjust the pressure value of the air compressor so that the water in the pressure tank flows into the rock fissure through valve a under a certain hydraulic pressure. During the initial injection, valves a, b, c and d are all opened; when water can flow into the water storage tank through valve b or valve c, the corresponding valve b or valve c is closed; valves a and d are kept open to maintain a constant water pressure and continuously inject water. After the flow meter reading is stable, the flow meter reading Q1 and the differential pressure gauge reading P1 are read; the pressure value of the air compressor is adjusted to adjust the differential pressure gauge reading to P2, and the corresponding flow meter reading Q2 is recorded. Repeating the above steps can obtain at least three sets of differential pressure-flow data, thereby calculating the permeability coefficient of the current rock fissure;
[0018] Step 4: Figure 5 As shown, the above two different types of rock fissures are subjected to soybean urease-induced calcium carbonate deposition grouting reinforcement and permeability reduction. The soybean urease solution is obtained by stirring soybeans, the soybean dregs are filtered out, the upper clear liquid is taken, and a calcium chloride solution with a concentration of 1.8-2.2 mol / L and a urea solution with a concentration of 1.8-2.2 mol / L are mixed in equal volumes to obtain a cementing solution; after the cementing solution and the urease solution are mixed, a liquid pump is used to inject the cementing solution into the rock fissure through valve 24 at a constant rate; during the initial injection, valves a, b, c and d are all opened; when the slurry can flow into the slurry recovery container through valve b or valve c, the corresponding valve b or valve c is closed, and the slurry is continuously injected until the slurry can flow into the slurry recovery container through valve a and valve d, then valve a and valve d can be closed, the slurry injection is stopped, and valves a, b, c and d are kept closed, so that the slurry is allowed to stand in the sample fissure for 8-14 hours to ensure that the slurry in the fissure is fully reacted to generate calcium carbonate deposition, so as to achieve the effect of cementing the rock fissure surface;
[0019] Step 5. After 8 to 14 hours, connect the seepage test system and slowly inject clean water into the sample cracks. Continue to inject until the slurry in the rock cracks is cleaned. At this time, turn on the light source and use a high-speed camera to take pictures of the cemented rock crack surface to analyze the deposition pattern, crystal size and cementation characteristics of calcium carbonate crystals in the sample crack surface. Use the method described in step 3 to test the permeability coefficient of the rock crack surface after soybean urease-induced calcium carbonate deposition grouting.
[0020] Step 6. Repeat step 1 or step 2, using rock fracture surfaces with different roughness, tension-type rock fractures with different fracture openings, or shear-type rock fractures with different shear displacements and openings to analyze the relationship between the grouting effect of soybean urease-induced calcium carbonate deposition and the rock fracture type and fracture parameters; repeat steps 4 and 5 to obtain the changes in the cementation position, size and permeability coefficient of calcium carbonate crystals in the rock fracture surface after at least three groutings, so as to obtain the anti-seepage effect of soybean urease-induced calcium carbonate deposition on tension-type or shear-type rock fractures.
[0021] Preferably, in step 4, the concentrations of the calcium chloride solution and the urea solution are both 2.0 mol / L.
[0022] Preferably, in step 4, the slurry is allowed to stand in the cracks of the sample for 12 hours.
[0023] Beneficial effects of the present invention:
[0024] 1) The upper rock test block made of transparent material was used to visualize the test process, and to further understand the process of soybean urease-induced calcium carbonate deposition on rock fissure plugging and permeability reduction;
[0025] 2) By using the upper shear box and the lower shear box to simulate the tension cracks and shear crack surfaces of rocks, the effect of soybean urease-induced calcium carbonate deposition on rock crack plugging and permeability reduction in different rock crack generation mechanisms can be better tested;
[0026] 3) When the lower shear box moves horizontally, it is sealed by the slurry sealing assembly, and the sealing state can be maintained even in the shear dislocation of the crack;
[0027] 4) The device can test the relationship between the plugging and seepage reduction effect of soybean urease-induced calcium carbonate deposition and the rock fracture type and fracture parameters, which is conducive to the development of soybean urease-induced calcium carbonate precipitation technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the shearing structure of the present invention;
[0029] Figure 2 It is a schematic diagram of the grouting reinforcement and seepage reduction structure of the present invention;
[0030] Figure 3 for Figure 2 A top view of
[0031] Figure 4 is a schematic diagram of the seepage test system;
[0032] Figure 5 It is a schematic diagram of the experiment of the present invention;
[0033] In the figure: 1-sample, 2-upper shear box, 3-horizontal connecting rod, 4-tightening bolt a, 5-vertical support rod, 6-tightening bolt b, 7-base, 8-horizontal rolling groove, 9-lower shear box, 10-end guide block, 11-end water sealing pressure plate, 12-end water sealing rubber pad, 13-side water sealing rubber pad, 14-side water sealing pressure plate, 15-fastening bolt, 16-pressure plate support frame, 17-fixing bolt, 18-hand crank push rod, 19-horizontal scale, 20-soybean urease solution, 21-upper clear liquid, 22-cementing liquid, 23-liquid pump, 24-valve a, 25-valve b, 26-valve c, 27-valve d, 28-slurry recovery container, 29-light source, 30-high-speed camera, 31-air compressor, 32-pressure tank, 33-water storage tank, 34 differential pressure gauge, 35-flow meter. DETAILED DESCRIPTION
[0034] In order to better understand the improvements made by the present invention relative to the prior art, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0035] like Figure 1 —3 shows a test device for sealing rock cracks using soybean urease-induced calcium carbonate deposition technology, which mainly consists of a sample 1, a crack simulation component and a slurry sealing component, wherein the sample 1 consists of an upper rock test block and a lower rock test block that match each other, the opposite surfaces of the upper rock test block and the lower rock test block are meshed with each other to simulate rock cracks inside a natural rock body, and the upper rock test block is made of a transparent material that is easy to observe, and the upper rock test block is preferably cast from a transparent resin material, and the lower rock test block is made of real rock material.
[0036] The fracture simulation assembly is mainly composed of an upper shear box 2, a lower shear box 9 and a base 7. The upper shear box 2 is used to clamp the upper rock test block, and the lower shear box 9 is used to hold the lower rock test block. When the upper shear box 2 and the lower shear box 9 are respectively installed on the upper and lower parts of the sample 1, a gap is left between the two to facilitate the mutual movement between the upper shear box 2 and the lower shear box 9. The upper shear box 2 is tightened and fixed to the upper rock test block by tightening bolts a 4. A rectangular observation port is provided on the top of the upper shear box 2 to cooperate with the transparent upper rock test block, so as to realize the visual observation of the slurry flow and calcium carbonate deposition inside the fracture surface.
[0037] The base 7 is provided with a vertical support rod 5 and a horizontal rolling groove 8, both of which are marked with scales. It is preferred that the surface of the vertical support rod 5 is marked with scales, and a horizontal scale 19 is provided at the edge of the horizontal rolling groove 8. The upper shear box 2 is slidably connected to the vertical support rod 5 through a horizontal connecting rod 3 with a sleeve at the end and fixed by tightening the locking bolt b 6 set in the sleeve, so that the upper rock test block can move up and down relative to the lower rock test block to simulate the tension type crack of the rock block, wherein four vertical support rods 5 are provided corresponding to the upper shear box 2, so that the movement of the upper shear box 2 is accurate and stable. A roller is installed in the horizontal rolling groove 8, which has lower precision requirements than a ball bearing and has a low cost of protection and replacement. The lower shear box 9 can roll on the horizontal rolling groove 8 through a hand-cranked push rod 18 to realize that the lower rock test block can move left and right relative to the upper rock test block to simulate the shear type crack of the rock block.
[0038] The slurry sealing assembly is mainly composed of end guide blocks 10, end water sealing pressure plates 11, end water sealing rubber pads 12, side water sealing rubber pads 13 and side water sealing pressure plates 14 arranged in pairs. The end guide block 10 is provided with a fluid channel inside and is fixedly installed at the left and right ends of the sample 1. The fluid channel is a right-angle fluid channel. The end water sealing rubber pad 12 is arranged between the end guide block 10 and the end water sealing pressure plate 11, and the end guide block 10 and the end water sealing pressure plate 11 are both split structures corresponding to the upper shear box 2 and the lower shear box 9. The end water sealing rubber pad 12 adopts an integrated structure and leaves a redundant amount bulging outward at the upper and lower split positions.
[0039] The side water-sealing rubber pad 13 and the side water-sealing pressure plate 14 are both arranged on the front and rear sides of the sample 1 to seal the gap between the upper shear box 2 and the lower shear box 9. The side water-sealing pressure plate 14 is preferably fixed and pressed by an "L"-shaped pressure plate support frame 16 and a fastening bolt 15. The pressure plate support frame 16 is fixed to the base 7 by a fixing bolt 17. The left and right ends of the side water-sealing rubber pad 13 and the side water-sealing pressure plate 14 are both provided with extensions to ensure that when the lower shear box 9 moves to the left and right limit positions relative to the upper shear box 2, it can still flexibly overlap with the two ends of the end water-sealing rubber pad 12 to form a closed storage cavity. The end water-sealing rubber pad 12 is preferably made of industrial rubber sheet with a thickness of 3 mm, which is flexible and fold-resistant, has a flat surface, good sealing performance, and is acid and alkali resistant. The side water-sealing rubber pad 13 is preferably made of silicone material, which is softer than the end water-sealing rubber pad 12. To ensure a better sealing effect, the thickness is 10 mm. Under the pressure of the side water sealing pressure plate 14, the side of the crack can be fully sealed, and because the side water sealing rubber pad 13 is flexible, when the rock crack is sheared, the side water sealing rubber pad 13 can still deform and maintain good sealing. At the same time, because the end water sealing rubber pad 12 has greater toughness and rigidity than the side water sealing rubber pad 13, under the pressure of the side water sealing pressure plate 14, the boundary of the end water sealing rubber pad 12 can form a tight overlap with the side water sealing rubber pad 13, and this overlap can also maintain good sealing with the shear displacement of the crack.
[0040] A test method for plugging rock fissures by using soybean urease-induced calcium carbonate deposition technology, using the above-mentioned soybean urease-induced calcium carbonate deposition technology for rock testing device, comprising the following steps:
[0041] Step 1: Simulate the tension type crack opening. Install the sample 1 on the crack simulation assembly, keep the upper rock test block and the lower rock test block in a natural meshing state, regard the crack as being in the initial closed state, read the scale value h0 of the upper shear box 2 relative to the vertical support rod 5, and h0 is preferably the average value of the scale values of the four sleeves on the corresponding vertical support rod 5.
[0042] Keep the lower shear box 9 and the lower rock test block stationary, vertically lift the upper shear box 2 and the upper rock test block, read the scale value h0′ of the upper shear box 2 relative to the vertical support rod 5, and thus obtain the tension type rock fracture with a fracture opening of Δh=h0′-h0;
[0043] Step 2: Simulate the opening of shear-type cracks. Install the specimen 1 on the crack simulation assembly, keep the upper rock test block and the lower rock test block in a natural meshing state, regard the crack as being in the initial closed state, read the scale value h0 of the upper shear box 2 relative to the vertical support rod 5, and read the horizontal scale value s0 of the horizontal rolling groove 8 corresponding to the left or right edge of the lower shear box 9.
[0044] The lower shear box and the lower rock block are gradually moved horizontally. Due to the roughness of the rock fracture surface, the horizontal displacement of the lower shear box 9 will also cause the upper shear box and the rock block to move vertically freely. It is necessary to read the scale value h0′ of the upper shear box 2 relative to the vertical support rod 5, and read the horizontal scale value s0′ of the horizontal rolling groove 8 corresponding to the left or right edge of the lower shear box 9. From this, the shear type rock fracture with a fracture shear displacement of Δs=s0′-s0 and a fracture opening of Δh=h0′-h0 is obtained.
[0045] Step 3: First test the permeability coefficient of the rock fissure before grouting reinforcement to form a control group. Use the seepage test system to adjust the pressure value of the air compressor 31 so that the water in the pressure tank 32 flows into the rock fissure through valve a24 under a certain hydraulic pressure. During the initial injection, valves a24, b25, c26 and d27 are all open. When water can flow into the water storage tank 33 through valve b25 or valve c26, close the corresponding valve b25 or c26; keep valve a24 and valve d27 open, maintain a constant water pressure, and continue to inject water. After the flow meter reading is stable, read the reading Q1 of the flow meter 35 and the reading P1 of the differential pressure meter 34. Adjust the pressure value of the air compressor 31, thereby adjusting the reading of the differential pressure meter 34 to P2, record the corresponding flow meter reading Q2, repeat the above steps, and you can get at least three sets of pressure difference-flow data, so as to calculate the permeability coefficient of the current rock fissure.
[0046] Step 4: Soybean urease-induced calcium carbonate deposition grouting reinforcement and permeability reduction are performed on the above two different types of rock fissures. Soybean urease solution 20 is obtained by stirring soybeans, and the dregs are filtered out. The upper clear liquid 21 is taken, and a calcium chloride solution with a concentration of 1.8-2.2 mol / L and a urea solution with a concentration of 1.8-2.2 mol / L are mixed in equal volumes to obtain a cementing liquid 22, wherein the concentrations of the calcium chloride solution and the urea solution are preferably 2.0 mol / L. After the cementing liquid 22 is mixed with the urease solution 21, a liquid pump 23 is used to inject it into the rock fissure through a valve 24 at a constant rate.
[0047] During the initial injection, valve a24, valve b25, valve c26 and valve d27 are all opened. When the slurry can flow into the slurry recovery container 28 through valve b25 or valve c26, the corresponding valve b25 or valve c26 is closed. The slurry is continuously injected until the slurry can flow into the slurry recovery container 28 through valve a24 and valve d27. Then valve a24 and valve d27 can be closed to stop injecting the slurry. The valves a24, valve b25, valve c26 and valve d27 are all closed. The slurry is allowed to stand in the cracks of the sample 1 for 8 to 14 hours, preferably 12 hours, to ensure that the slurry in the cracks fully reacts to generate calcium carbonate deposition, thereby achieving the effect of cementing the rock crack surface.
[0048] Step 5: After 8 to 14 hours, the seepage test system is connected to slowly inject clean water into the cracks of sample 1. The slurry after the reaction in the rock cracks is flushed clean by continuous injection. At this time, the light source 29 is turned on, and the high-speed camera 30 is used to take pictures of the cemented rock crack surface to analyze the deposition pattern, crystal size and cementation characteristics of calcium carbonate crystals in the crack surface of sample 1. The permeability coefficient of the rock crack surface after soybean urease-induced calcium carbonate deposition grouting is tested using the method in step 3.
[0049] Step 6: Repeat step 1 or step 2, using rock fracture surfaces with different roughness, tension-type rock fractures with different fracture openings, or shear-type rock fractures with different shear displacements and openings to analyze the relationship between the grouting effect of soybean urease-induced calcium carbonate deposition and the rock fracture type and fracture parameters. Repeat steps 4 and 5 to obtain the changes in the cementation position, size and permeability coefficient of calcium carbonate crystals in the rock fracture surface after at least three groutings, so as to obtain the permeability-blocking effect of soybean urease-induced calcium carbonate deposition on tension-type or shear-type rock fractures.
[0050] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A test device for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology, characterized in that: The invention comprises a sample (1), a fracture simulation component and a slurry sealing component, wherein the sample (1) is composed of an upper rock test block and a lower rock test block that match each other, and the upper rock test block is made of a transparent material; The crack simulation component comprises an upper shear box (2), a lower shear box (9) and a base (7); the upper shear box (2) is used to clamp the upper rock test block, the lower shear box (9) is used to hold the lower rock test block, and a gap is left between the upper shear box (2) and the lower shear box (9) when they are respectively installed on the upper and lower parts of the sample (1); a vertical support rod (5) and a horizontal rolling groove (8) are provided on the base (7); the vertical support rod (5) and the horizontal rolling groove (8) are both marked with scales; the upper shear box (2) and the vertical support rod (5) are slidably connected to realize that the upper rock test block can move up and down relative to the lower rock test block to simulate the tension type crack of the rock block; the lower shear box (9) can roll on the horizontal rolling groove (8) to realize that the lower rock test block can move left and right relative to the upper rock test block to simulate the shear type crack of the rock block; The slurry sealing assembly comprises an end flow guide block (10), an end water sealing pressure plate (11), an end water sealing rubber pad (12), a side water sealing rubber pad (13) and a side water sealing pressure plate (14) arranged in pairs; the end flow guide block (10) is provided with a fluid channel inside and is fixedly installed at the left and right ends of the sample (1); the end water sealing rubber pad (12) is arranged between the end flow guide block (10) and the end water sealing pressure plate (11); and the end flow guide block (10) and the end water sealing pressure plate (11) both correspond to the upper shear box (2) and the lower shear box (9) and adopt a split structure; the end water sealing The water rubber pad (12) adopts an integrated structure and has a redundant amount bulging outward at the upper and lower split positions; the side water sealing rubber pad (13) and the side water sealing pressure plate (14) are both arranged on the front and rear sides of the sample (1) to seal the gap between the upper shear box (2) and the lower shear box (9); the left and right ends of the side water sealing rubber pad (13) and the side water sealing pressure plate (14) are both provided with extensions to ensure that when the lower shear box (9) moves to the left and right extreme positions relative to the upper shear box (2), it can still flexibly overlap with the two ends of the end water sealing rubber pad (12) to form a closed storage cavity.
2. The test device for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology according to claim 1, characterized in that: The upper rock test block is cast with transparent resin material, and the lower rock test block is made of real rock material.
3. The test device for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology according to claim 1, characterized in that: The upper shear box (2) is fixedly secured to the upper rock test block by means of a locking bolt a (4); a rectangular observation port is provided on the top of the upper shear box (2) and cooperates with the transparent upper rock test block to realize visual observation of the slurry flow and calcium carbonate deposition inside the fracture surface; the upper shear box (2) is slidably connected to the vertical support rod (5) by means of a horizontal connecting rod (3) with a sleeve at the end thereof, and is fixed by tightening a locking bolt b (6) disposed in the sleeve; four vertical support rods (5) are provided corresponding to the upper shear box (2).
4. The test device for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology according to claim 1, characterized in that: A roller is installed in the horizontal rolling groove (8) to realize the horizontal movement of the lower shear box (9), and the horizontal movement of the lower shear box (9) is realized by a hand-cranked push rod (18).
5. The test device for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology according to claim 1, characterized in that: The surface of the vertical support rod (5) is marked with scales, and a horizontal scale (19) is provided at the edge of the horizontal rolling groove (8).
6. The test device for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology according to claim 1, characterized in that: The side water sealing pressure plate (14) is fixed and compressed by an L-shaped pressure plate support frame (16) and a fastening bolt (15), and the pressure plate support frame (16) is fixed to the base (7) by a fixing bolt (17).
7. The test device for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology according to claim 1, characterized in that: The end water-sealing rubber pad (12) is made of an industrial rubber plate, and the side water-sealing rubber pad (13) is made of a silica gel material.
8. A test method for plugging rock fissures using soybean urease-induced calcium carbonate deposition technology, characterized in that: A test device for plugging rock fissures using a soybean urease-induced calcium carbonate deposition technology according to any one of claims 1 to 7, comprising the following steps: Step 1, simulating the tension type crack opening; installing the sample (1) on the crack simulation component, keeping the upper rock test block and the lower rock test block in a natural meshing state, considering that the crack is in an initial closed state at this time, and reading the scale value h0 of the upper shear box (2) relative to the vertical support rod (5); keeping the lower shear box (9) and the lower rock test block still, vertically lifting the upper shear box (2) and the upper rock test block, and reading the scale value h0′ of the upper shear box (2) relative to the vertical support rod (5), thereby obtaining a tension type rock crack with a crack opening of Δh=h0′-h0; Step 2, simulating the opening of a shear-type fracture; installing the specimen (1) on a fracture simulation assembly, keeping the upper rock test block and the lower rock test block in a natural meshing state, considering the fracture to be in an initial closed state at this time, reading the scale value h0 of the upper shear box (2) relative to the vertical support rod (5), and reading the horizontal scale value s0 of the horizontal rolling groove (8) corresponding to the left or right edge of the lower shear box (9); gradually moving the lower shear box and the lower rock block horizontally, reading the scale value h0′ of the upper shear box (2) relative to the vertical support rod (5), and reading the horizontal scale value s0′ of the horizontal rolling groove (8) corresponding to the left or right edge of the lower shear box (9), thereby obtaining a shear-type rock fracture with a fracture shear displacement of Δs=s0′-s0 and a fracture opening of Δh=h0′-h0; Step 3: First, test the permeability coefficient of the rock fissure before grouting reinforcement to form a control group; use a seepage test system to adjust the pressure value of the air compressor (31) so that the water in the pressure tank (32) flows into the rock fissure through valve a (24) under a certain hydraulic pressure. During the initial injection, valve a (24), valve b (25), valve c (26) and valve d (27) are all opened; when water can flow into the water storage tank (33) through valve b (25) or valve c (26), the corresponding valve is closed. b (25) or valve c (26); keep valve a (24) and valve d (27) open, maintain a constant water pressure, and continue to inject water. After the flow meter reading is stable, read the reading Q1 of the flow meter (35) and the reading P1 of the differential pressure meter (34); adjust the pressure value of the air compressor (31), thereby adjusting the reading of the differential pressure meter (34) to P2, and record the corresponding flow meter reading Q2. Repeat the above steps to obtain at least three sets of pressure difference-flow data, thereby calculating the permeability coefficient of the current rock fracture; Step 4: Soybean urease-induced calcium carbonate deposition grouting reinforcement and permeability reduction are performed on the two different types of rock fissures mentioned above. Soybean urease solution (20) is obtained by stirring soybeans, and the soybean dregs are filtered out. The upper clear liquid (21) is taken, and a calcium chloride solution with a concentration of 1.8 to 2.2 mol / L and a urea solution with a concentration of 1.8 to 2.2 mol / L are mixed in equal volumes to obtain a cementing liquid (22); after the cementing liquid (22) and the urease solution (21) are mixed, a liquid pump (23) is used to inject the cementing liquid (22) into the rock fissure through a valve 24 at a constant rate; during the initial injection, valve a (24), valve b (25), valve c (26) and valve d (27) are all opened. When the slurry can flow into the slurry recovery container (28) through valve b (25) or valve c (26), close the corresponding valve b (25) or valve c (26), and continue to inject the slurry until the slurry can flow into the slurry recovery container (28) through valve a (24) and valve d (27), then close valve a (24) and valve d (27), stop injecting the slurry, keep valve a (24), valve b (25), valve c (26) and valve d (27) closed, and allow the slurry to stand in the cracks of the sample (1) for 8 to 14 hours to ensure that the slurry in the cracks fully reacts to generate calcium carbonate deposition, thereby achieving the effect of cementing the rock crack surface; Step 5: After 8 to 14 hours, connect the seepage test system and slowly inject clean water into the cracks of the sample (1). Continue to inject until the slurry in the rock cracks is cleaned. At this time, turn on the light source (29) and use a high-speed camera (30) to take pictures of the cemented rock crack surface to analyze the deposition pattern, crystal size and cementation characteristics of calcium carbonate crystals in the crack surface of the sample (1). Use the method described in step 3 to test the permeability coefficient of the rock crack surface after soybean urease-induced calcium carbonate deposition grouting. Step 6. Repeat step 1 or step 2, using rock fracture surfaces with different roughness, tension-type rock fractures with different fracture openings, or shear-type rock fractures with different shear displacements and openings to analyze the relationship between the grouting effect of soybean urease-induced calcium carbonate deposition and the rock fracture type and fracture parameters; repeat steps 4 and 5 to obtain the changes in the cementation position, size and permeability coefficient of calcium carbonate crystals in the rock fracture surface after at least three groutings, so as to obtain the anti-seepage effect of soybean urease-induced calcium carbonate deposition on tension-type or shear-type rock fractures.
9. The method for testing the soybean urease-induced calcium carbonate deposition technology for plugging rock fissures according to claim 7, characterized in that: In step 4, the concentrations of the calcium chloride solution and the urea solution are both 2.0 mol / L.
10. The method for testing the soybean urease-induced calcium carbonate deposition technology for plugging rock fissures according to claim 7, characterized in that: In step 4, the slurry is left in the cracks of the sample (1) for 12 hours.
Citation Information
Patent Citations
Crack grouting visualization tester under complex conditions
CN102419303A
Servo controlled rock fracture shear seepage test sealing device
CN107389525A
Device and method for simulating visual gap seepage by magnetic fluid
CN110296928A
Rock shearing-seepage testing machine and testing method thereof
CN110687274A
Image numeralization experiment device for rock fracture visual seepage opening degree testing and using method
CN111175213A
Cited By
Grouting test device and method for filling type crack of deep underground rock mass
CN120063982A
Sealing device for rock mass shear seepage test
CN120141995A
Method for determining plugging performance of filler
CN121898984A